Quality education for all in an ideas-informed society: exploring idea-engagement amongst friendship networks and how education can prevent idea “echo-chambers” - Chris Brown; Jana Gross Ophoff; Graham Handscomb (Quality Education for All)
Purpose – The purpose of this study is to begine to address this question. The concept of the ideas-informed society (IIS) represents a desired situation in which citizens actively and critically engage with new ideas, developments and claims to truth. Its successful actualisation is dependent on high-quality educational opportunity at all stages of the life course. Social networks represent our connections to one another. Features of our social networks impact on how we engage with ideas. For instance, homophily dictates that individuals form networks with others seen as being like themselves. A key question, however, is whether there are forms of homophily that, by the nature of those they bring together, promote ideas engagement by individuals and the implications of consequent networks for the IIS? Design/methodology/approach – This study re-analysed survey data from 1,000 voting-age citizens in England. Focusing on friendship networks, the authors used a structural equation model approach to explore the existence and potency of homophilic friendship networks; whether such networks drive respondents’ ideas-engagement with friends; and whether ideas discussions with friends impacts on the importance respondents place on staying up to date. Findings – Political homophily has the strongest influence on whether people discuss new ideas with their friends (ES = 0.326, p < 0.01). In turn, ideas discussion has a significant impact on the extent to which people value engaging with ideas (ES = −0.345, p < 0.01). Originality/value – The authors consider whether ideas-related discussion within politically homophilous networks is problematic for the IIS and what is required from education systems if we are to build individuals’ capacity to engage with ideas while escaping echo chambers.